Thermosensitive Poly(DHSe/PEG/PPG Urethane)-Based Hydrogel Extended Remdesivir Application in Ophthalmic Medication - Sennan Xu; Lingjie Ke; Sichen Zhao; Zhiguo Li; Yang Xiao; Yunlong Wu; Jie Ren; Yan Qiu (MDPI AG, 2021)
The spread of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the coronavirus disease 2019 (COVID-19) outbreak beginning in March 2020. Currently, there is a lack of suitable dose formulations that interrupt novel coronavirus transmission via corneal and conjunctival routes. In the present study, we developed and evaluated a thermosensitive gelling system based on a selenium-containing polymer for topical ocular continuous drug release. In detail, di-(1-hydroxylundecyl) selenide (DHSe), poly(ethylene glycol) (PEG), and poly(propylene glycol) (PPG) were polymerized to form poly(DHSe/PEG/PPG urethane). The polymer was used to carry poorly water-soluble remdesivir (RDV) at room temperature to form the final thermosensitive in situ gel, which exhibited a typical sol-gel transition at 35 °C. The formed polymer was further characterized by rheology, thermology, and scanning electron microscopy. In vitro release studies and in vivo retention and penetration tests indicated that the thermogel provided the prolonged release of RDV. The RDV-loaded in situ gel was proven to be non-biotoxic against human corneal epithelial cells, with good ocular tolerance and biocompatibility in rabbit eyes.